(untitled) (Physical Education, Health and Social Sciences, 2026)
Healthcare development projects play a critical role in improving healthcare infrastructure, service delivery, and the adoption of new technologies. However, many healthcare projects face significant implementation challenges, including coordination problems, communication barriers, and resistance to organizational change. Leadership practices and organizational culture have therefore emerged as important factors influencing project success in healthcare environments. This study examines the effect of transformational leadership on healthcare project success while investigating the mediating role of perceived organizational trust. Drawing on Social Exchange Theory, the study proposes that transformational leadership behaviors encourage employees to develop trust in their organization, which strengthens collaboration and commitment to project objectives. A quantitative cross-sectional research design was employed, and data were collected from healthcare professionals involved in project implementation in hospitals across Punjab, Pakistan. Structural Equation Modeling (SEM) was used to analyze the relationships among transformational leadership, organizational trust, and healthcare project success. The results indicate that transformational leadership has a significant positive effect on healthcare project success by improving teamwork, communication, and employee engagement in project activities. The findings also reveal that transformational leadership significantly enhances employees’ perceptions of organizational trust. Furthermore, organizational trust positively influences healthcare project success and partially mediates the relationship between transformational leadership and project outcomes. This suggests that transformational leadership contributes to project success not only directly but also indirectly by fostering a trust-based organizational environment that promotes cooperation among healthcare professionals. The study contributes to the literature by integrating leadership theory and organizational trust within a project management framework for healthcare settings. The findings provide practical implications for healthcare administrators and policymakers by highlighting the importance of strengthening transformational leadership practices and building organizational trust to improve the implementation and performance of healthcare development projects.